IMPLEMENTASI MANAJEMEN SECURITY TERHADAP CYBER CRIME DI INDONESIA - Rivaldi Rasqi Al Zahabi; Sabni Gilang Permana, Angga wicaksana, Abdul Nasar, Fiqih Assidiq Ramadhan (ADISAM PUBLISHER, 2025)
Cybercrime is a felonious act that utilizes computers or the Internet as its primary means of prosecution. InIndonesia, enterprises about cybercrime are raising, egging the government to introduce the Cybercrime Law. mindfulness ofdigital security pitfalls is also adding , especially regarding the vulnerability of particular information to abuse by reckless parties. This situation is aggravated by the lack of sweats to cover data in Indonesia, leading to a series of playing incidents and data breaches. These events include the hacking of social media accounts and identity theft, posing serious implicit impacts similar as particular data violations, highway robbery, and online fraud. The significance of regulations to guard particular data is decreasingly honored by the Indonesian government, as reflected in their sweats to draft and legislate Law Number 27 of 2022 on Cybercrime. This step demonstrates a serious commitment to gradationally enhancing the protection of particular data, with the stopgap of perfecting digital security and reducing the threat of cybercrime in Indonesia